STUDI ETNOMEDISIN PADA MASYARAKAT DI KAMPUNG DEMI, KABUPATEN BANTUL, YOGYAKARTA - Fitra Romadhonsyah; Putrilia Dyah Puspitasari; Shubhi Mahmashony Harimurti; Arde Toga Nugraha (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Indonesian people are known to have traditional medicine using medicinal plants based on heritage or stories passed down from ancestors and are immaterial or mythical. The lack of documentation makes the use of traditional medicine not maximized. This study aims to determine the knowledge of the community regarding the use of medicinal plants as a treatment and to determine the types of plants used for treatment in Kampung Demi, Bantul, Yogyakarta. The sampling technique used was purposive sampling with observation using a questionnaire instrument. The number of respondents who met the inclusion criteria was 51 respondents. The result data was analyzed using ICF (Informant Consensus Factor). The results showed 97.12% of respondents understood the benefits of medicinal plants, 64.70% of respondents stated that understanding traditional medicine was hereditary from the family, 49.02% of respondents got medicinal plants from their own yard, 74.51% of respondents often used traditional medicine compared to conventional medicine, and there were 11 types of medicinal plants used by respondents for treatment. The categories of diseases treated with the most types of medicinal plants were ten types of medical diseases (ICF = 1.0) and two types of magical/non-medical habits (ICF = 1.0).